(untitled) - Filová, Eva; Dávid, Andrej; Sosedová, Jarmila (Doprava a spoje, 2012)
Tourist industry in the content of the development of water tourism in the conditions of the Slovak Republic. The rating of selected tourism centres - micro region Medzibodrožie, Liptov, Orava, micro region Zemplínska Šírava, Dolné Považie - related the rivers / water areas (the rivers such as the Bodrog and the Váh, water areas like Liptovská Mara, Orava dam, Zemplínska Šírava) through multi objective analysis or proportionality - index method.